Effect of TMP-based-cottonseed oil-biolubricant blends on tribological behavior of cylinder liner-piston ring combinations. (15th October 2020) - Gul, M.; Zulkifli, N.W.M.; Masjuki, H.H.; Kalam, M.A.; Mujtaba, M.A.; Harith, M.H.; Syahir, A.Z.; Ahmed, Waqar; Bari Farooq, Abdul
Highlights: TMP-based-Cotton biolubricant was synthesized from cottonseed oil and its blends were prepared with commercially available lubricant SAE-40. All cotton biolubricant blends meet ISO viscosity grade requirements. Wear and frictional characteristics of cotton biolubricant blends were evaluated by HFRR and 4-ball tribo-tester for engine cylinder-liner and piston ring applications. COF between sliding surfaces reduces with cotton biolubricant addition in SAE-40. CBL-10 showed better wear and friction characteristics than SAE-40 and other blends. Abstract: Cottonseed oil-based biolubricant was synthesized by the TMP-based transesterification process. 10–50% by volume blends of TMP-based cotton-biolubricant and SAE-40 were prepared and tested on the high-frequency-reciprocating-rig with engine cylinder-liner and piston-ring combination to investigate their tribology. While tribological characteristics were also evaluated by four-ball tribo-testers at high constant load of 785 N. 10% addition of cotton-biolubricant showed the lowest friction and wear as compared to SAE-40 but>10% volume of cotton biolubricant in blend increased the wear and friction considerably as tested by both HFRR and four-ball. Hence, 10% addition of TMP-cotton-biolubricant can be utilized as an energy-saving lubricant additive to partially reduce the dependency on petroleum-based lubricant for automotive engine application.